Human-centred health-care environments: a new framework for biophilic design - Tekin, Bekir Huseyin; Urbano Gutiérrez, Rosa (Frontiers in Medical Technology, 2023)
Increasing research corroborates that the qualities of the setting in which a patient receives healthcare positively influence health outcomes. Therefore, it has become progressively important to review the concept of therapeutic environments, as places where patients are treated with the most advanced medicine and technology, but also support their users in psychological, emotional and social terms. This quest for the optimal healing environment brings to the forefront the need to include other parameters in our design briefs, where the application of biophilic design proves to be paramount, as exposure to nature is associated with multiple health benefits. However, current biophilic design frameworks fail to provide efficient guidance, as their design recommendations don’t differentiate the level of value of each design parameter for each building programme and context. Our position is that a biophilic design framework can only be efficient if it is adapted to specific building functions and is geographically and culturally contextualized. This study assessed the application of biophilic design in therapeutic environments for cancer patients in the UK, and provided a revised conceptual framework that can more efficiently guide designers and policies in future interventions. This framework was informed by synthesised analyses from healthcare environments on the user’s experiences, and primary data obtained from semi-structured interviews with architects and managers, which was then benchmarked against scientific data about the impact of biophilic design on humans. This comprehensive approach helped to identify and rank those biophilic design parameters that appear the most critical for promoting and supporting health and wellbeing in cancer healthcare settings and provided an up-to-date compilation of crucial design actions to enact the necessary change in future research and design practice.